Jews and Muslims in seventeenth-century discourse: from religious enemies to allies and friends - Waite, Gary K. (Routledge, 2019)
Jews in England and the Netherlands, 1550-1620: anti-semitism, religious polemics, and realpolitique -- Christian Nonconformists and Jews, 1540-1650 -- Muhammad: Christian fantasies of the Prophet and the Qur'an -- Moors and Moriscos, 1550-1620 -- Europeans and the Ottomans: fantasy and reality, 1610-1648 -- Millenarian dreams, ecumenical prophets, and the lost tribes found, 1648-65 -- The Sabbatai Zevi experience: Jews, Christians, and Muslims, 1666-1700